Current Trends in Historical Sociolinguistics - Russi, Cinzia (De Gruyter, 2016)
The volume collects original studies highlighting contemporary trends in historical sociolinguistics, as well as current research on the relationship between sociolinguistics and historical linguistics, social motivations of language variation and change, and corpus-based studies. Distinctive features of the book, which make it appealing to a wider audience, are the interdisciplinary nature of the chapters and the range of languages addressed.